PERLINDUNGAN SAKSI PIDANA MENURUT HUKUM PIDANA INDONESIA DAN HUKUM PIDANA ISLAM - Adam Sani (Universitas Teuku Umar, 2016)
The purpose of research and study to find out and explain the concept of witness protection in criminal cases under Indonesian criminal law and the criminal law of Islam and to explain the concept of comparative analysis on the protection of witnesses in criminal cases in the criminal law Indonesia.Penelitian this method of normative legal research, the study in the form of legislation, legal principles, norms, and others. In the discussion of this thesis is done through a comparative descriptive approach (comparison), which describe and analyze data on the protection of witnesses, according to the conception of Indonesian criminal law and criminal law of Islam. The results showed that first, the concept of witness protection in the Indonesian criminal law and the criminal law of Islam has much in common they both protect the witnesses have efforts to comply with the provision of security to the witness so that in spite of the threats of others both a threat to life, honor, finances and family. But what sets it apart is the legal basis, terms and various witnesses, the agency that protects witnesses and witness protection. Suggested to the parties that have the authority to order the witness protection sincere and serious in protecting witnesses in accordance with what is stipulated in the regulations.Keywords; witness protection, criminal law of Indonesia, Islamic law